CRITERION VALIDITY OF A VOLLEYBALL SERVE-SPECIFIC CORE SELF-EVALUATIONS SCALE: RELATIONSHIP BETWEEN SERVE EFFICACY, EFFECTIVENESS AND SELF-ASSESSMENT IN INFANT FEMALE BRAZILIAN ATHLETES - Thais do Amaral Machado; Fernanda Patricia Valentim; Joice Mara Facco Stefanello (Journal of Physical Education)
ABSTRACT The aim of this study was to evaluate the relationship between self-assessment of volleyball serves and the effectiveness and efficacy of this skill. Two female volleyball teams of the infant category, with a mean age of 14.63 ± 0.5 years and a playing experience of 4.92 ± 1.87 years, participated in the study. A Volleyball Serve-Specific Self-Assessment Scale was applied and technical scout of the serve was performed. The results showed differences in effectiveness between team A (37.26 ± 19.38) and team B (53.89 ± 14.18) (p = 0.02) and in efficacy between team A (91 50 ± 5.51) and team B (96.21 ± 4.46) (p = 0.02). There was also a difference in self-assessment between team A (45.20 ± 5.11) and team B (41.78 ± 3.19) (p = 0.05). A moderate correlation (r = 0.65, p = 0.00) was observed between self-assessment and years of practice in both teams. In conclusion, the team that won first place was more effective and efficacious in executing the serve.